High grade B-cell lymphoma with rearrangements of MYC and BCL2 and/or BCL6: Double hit and triple hit lymphomas and double expressing lymphoma - Rosenthal, Allison (Blood Rev, 2016)
Diffuse large B-cell lymphomas with aberrations in MYC, BCL2 and/or BCL6 by genetic alterations or protein expression represent a group of high grade B-cell lymphomas with inferior outcomes when treated with standard RCHOP chemotherapy. As a result, intensified induction regimens have been suggested in an effort to improve outcomes. Conclusions to date have largely been drawn from retrospective data although prospective data is slowly starting to emerge. Chemoimmunotherapy refractoriness is problematic and relapse rates are high. Patients with double hit lymphoma appear to have increased risk of CNS involvement and prophylaxis is recommended. There is insufficient evidence available to date to strongly recommend for or against consolidative stem cell transplant in this population. Collaborative clinical trials will be needed to establish a preferred therapeutic regimen and an appropriate standard of care in this unique group of patients with DLBCL.